Pengaruh Suku Bunga Sbi Dan Kurs Dollar Terhadap Harga Saham Di BEI - Achmad, Noor; Liana, Liana (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2012)
SBI interest rate is yield of investment in the form of Sertifikat Bank Indonesia (SBI) which is determined by Bank Indonesia. Dollar exchange rate is relative price of Dollar against Rupiah. Certificates of Bank Indonesia as free risk investment instrument and Dollar exchange rate are consideration factors before investing in stock market in the form of shares so that stock prices will be influenced by those two variables. This study used the monthly data of SBI Interest Rates and semimonthly Dollar Exchange Rates and they are officially recorded in Bank Indonesia. The monthly closing price of IHSG was used as stock price data. This study used data of 2006 â 2010 and was processed by utilizing SPSS 17.0. From this study it can be concluded that SBI interest rate has strong correlation, has negative and significant influence, on stock prices. SBI interest rate has weak correlation, has negatif but not significant influence, on Dollar exchange rate. From the study of other factors that affect Dollar exchange rate, it can be found out that Dollar exchange rate is significantly affected by the balance of payments. Dollar exchange rate has moderate correlation, has negativeand significant influence, towards stock prices. SBI interest rate and Dollar exchange rate simultaneously have strong correlation, have negative and significant influence, towards stock prices.